Retrospective Echocardiographic Analysis of West Syndrome During Adrenocorticotropic Hormone Therapy - Ikuta, Yoji; Miura, Masaru; Goto, Tomohide; Miyama, Sahoko (Frontiers in Pediatrics, 2022)
Background: Ventricular hypertrophy is a well-known side effect of adrenocorticotropic hormone (ACTH) therapy in patients with West syndrome (WS), but there are only a few reports of echocardiographic evaluation of these patients’ diastolic function. Methods: The present, retrospective study analyzed echocardiographic findings in 26 patients with WS treated with ACTH therapy between April 2010 and December 2014. The therapy protocol involved administering tetracosactide acetate 0.01 - 0.0125 mg/kg via intramuscular injection once a day for weeks 1-2, and then gradually tapered off. Echocardiographic evaluation was done before treatment initiation, and at weeks 1, 2, and 4 after the initiation of treatment. Results: The systolic and diastolic blood pressure values were elevated at week 1 after commencement of the therapy and remained elevated throughout its duration. Both the interventricular septal end-diastolic thickness and left ventricular posterior wall end-diastolic diameter increased in thickness at week 1 and remained thickened. None of the patients experienced heart failure or systolic dysfunction. Early diastolic mitral flow velocity (E) / early diastolic mitral annular velocity (E’) increased at week 1 and remained high at weeks 2 and 4. The E wave deceleration time (DcT) was prolonged at week 2 and returned to the baseline at week 4. Conclusion: Increased ventricular wall thickness, decreased diastolic capacity, and elevated BP were noted in children with WS during ACTH therapy. Cardiac function, including ventricular wall thickness and diastolic function, should be monitored during ACTH therapy. E/E’ and DcT are useful in evaluating diastolic function.